Environmental disaster in the northeast coast of Brazil: Forensic geochemistry in the identification of the source of the oily material. (November 2020) - de Oliveira, Olívia M.C.; de S. Queiroz, Antônio F.; Cerqueira, José R.; Soares, Sarah A.R.; Garcia, Karina S.; Filho, Aristides Pavani; de L. da S. Rosa, Maria; Suzart, Caroline M.; de L. Pinheiro, Liliane; Moreira, Ícaro T.A.
Abstract: The characterization of petroleum or its products spilled in the environment in relation to its source rocks is an important tool to assist in the resolution of issues of environmental impact and legal responsibility since it clarifies the possible region or the producing country of that type of petroleum. This article analyzes the application of analytical techniques for petroleum geochemistry to identify the type and origin of oily material collected from beaches in Northeast Brazil in 2019. Samples of the oily material collected on the beaches in the states of Bahia and Sergipe were analyzed and for comparison purposes, samples of crude oils produced in Brazil, Middle East, Nigeria and Venezuela were also analyzed. The analytical results showed that the oily material that reached the beaches has geochemical characteristics compatible with those of the Venezuelan oil, indicating it was severely weathered or a product made with heavy oil produced. Highlights: Geochemistry analyses and multivariate statistics were used to identify the origin. Saturated biomarkers and δ 13 C were more useful for spill-oil source correlation. Oily material has characteristics that correlate it with oil of Venezuelan origin.